Adolescents' problematic internet and smartphone use in (cyber)bullying experiences: A network analysis. Issue 1 (16th December 2022) - Blinka, Lukas; Stašek, Andrea; Šablatúrová, Nika; Ševčíková, Anna; Husarova, Daniela
Abstract : Background: This study investigates both offline and online bullying perpetration and victimization in association with problematic internet use (PIU) and problematic smartphone use (PSU), while also considering the related psychosocial difficulties. Methods: A total of 3939 adolescents (49.4% boys, aged 13–15 years) from a representative sample of schools in Slovakia was obtained from the Health Behavior in School‐aged Children (HBSC) project in 2018. Due to the lack of similar complex research and the expected mutual associations among the constructs, we compared exploratory network models that provided separate estimates for boys and girls. Results: The constructs formed similarly clustered networks for both genders, with a few notable differences. Unlike PIU, PSU was not associated with bullying experiences in boys or girls; however, PSU and PIU were partially related in girls. Bullying experiences formed a strong cluster in both networks. Two strong bridges were identified, and they are potential candidates for intervention in both boys and girls: first, traditional bullying victimization connected the cluster of bullying experiences to psychosocial difficulties; and, second, frequently missing sleep or meals due to internet use (behavioral salience) that is connected to the bullying cluster with PIU. Conclusions: The findings offer an indication for the preventive and interventive work of practitioners who deal with adolescents, as well as complex gender comparisons for the mutual relations of problematic internet and smartphone use, bullying experiences, and the psychosocial difficulties of youth. This study provides evidence that problematic digital media can play a role in bullying experiences irrespective of whether bullying happens offline or online.